2012
DOI: 10.3390/molecules17055592
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Synthesis Under Solvent-Free Conditions and Spectral Studies of Some Mesoporphyrinic Complexes

Abstract: Abstract:A series of A 3 B and A 4 type mesoporphyrinic complexes were synthesized with superior yields using microwave irradiation under solvent-free conditions. The structures of the complexes were confirmed using elemental analysis, FT-IR, UV-Vis, EPR and NMR spectral data. The influence of environmental polarity on spectral properties of the mesoporphyrinic complexes was investigated. The obtained results indicate that the shape of absorption and fluorescence spectra does not depend on the solvent polarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The changes observed in the spectral behavior were in agreement with our previous results obtained for other unsymmetrical porphyrins [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Comparison of the absorption spectral parameters indicated that they were not significantly affected either by the type of peripheral substituents of the porphyrinic core, or by environmental polarity.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The changes observed in the spectral behavior were in agreement with our previous results obtained for other unsymmetrical porphyrins [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Comparison of the absorption spectral parameters indicated that they were not significantly affected either by the type of peripheral substituents of the porphyrinic core, or by environmental polarity.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, we selected for this study the synthesis and evaluation of A 3 B isomer complexes with zinc or copper ions. The A 4 type metalloporphyrins have been described by us previously [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that localization at a subcellular level of the tetrapyrrolic structure is directly influenced by the polarity of the molecule and by the type of metallic ion [21,22], our research has been focused on obtaining porphyrins with various degrees of hydrophobic/hydrophilic substitutions that favor their uptake by cellular targets [23,24,25,26,27,28,29,30]. As a continuation of our research, in this study we describe the synthesis of some new asymmetrical tetrapyrrolic complexes, Zn(II)-5-(3-hydroxyphenyl)-10,15,20-tris-(4-acetoxy-3-methoxyphenyl)porphyrin ( P1 ) and Cu(II)-5-(3-hydroxyphenyl)-10,15,20-tris-(4-acetoxy-3-methoxyphenyl)porphyrin ( P2 ) (Figure 1), their spectral properties and a preliminary in vitro evaluation focused on their dark toxicity in the context of their potential use in the diagnosis and PDT of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing our researches regarding amphiphilic porphyrins with biomedical applications, [17][18][19][20][21][22][23][24][25][26][27][28][29], in this study we synthesized a new A 2 B 2 type porphyrinic complex, Zn(II)-5,15-bis-(4-hydroxy-3-methoxyphenyl)-10,20-bis-(4-carboxymethylphenyl)porphyrin (Zn(II)P) ( fig. 1), and assessed its effect on the transmembrane potential of L929 cultured cells.…”
mentioning
confidence: 99%